Chinese school teachers' conceptions of high-stakes and low-stakes assessments: an invariance analysis. Issue 4 (3rd July 2020) - Chen, Junjun; Teo, Timothy
ABSTRACT: The study investigated teachers' conceptions of high-stakes and low-stakes assessments with a sample of 1, 013 school teachers from China. In general, the assessment model indicated that school teachers in this study agreed with the most factors. They demonstrated a broad understanding of the improvement, evaluation, control, irrelevance, and challenges of assessment for a range of purposes. Multi-group confirmatory factor analysis for high-stakes vs low-stakes found that Chinese teachers perceived improvement, school accountability and examination purposes as highly positively correlated, though accountability was weakly correlated with irrelevance. Further, these teachers showed favourable attitudes toward low-stakes assessments which are believed more indicative of learning, teaching, examination, and school accountability. These results indicate that it is an appropriate option to adopt low-stakes assessments to remedy the unintended effects of high-stakes assessments in China. Possible explanations for major results are discussed, which may provide implications for other educational contexts.